Pengaruh Kredibilitas Influencer dan Fitur Live Shopping terhadap Niat Beli Gen Z Dimediasi Kepercayaan pada Platform Tiktok - Muhammad Fachri Siregar; Diena Noviarini; Meta Bara Berutu (Indo Publishing, 2026)
This study aims to examine the influence of influencer credibility and Live Shopping features on Generation Z's purchase intention, with trust serving as a mediating variable on the TikTok platform. A quantitative approach with a survey method was employed. The research population consisted of Generation Z residing in Jakarta, who actively use TikTok and have watched Live Shopping sessions and made purchases through TikTok Shop within the last six months. A purposive sampling technique was applied, resulting in 180 respondents. Data were analyzed using PLS-SEM with SmartPLS 4 software. The findings reveal that influencer credibility positively affects purchase intention, Live Shopping features positively influence purchase intention, and Live Shopping features positively affect trust. Furthermore, trust has a significant effect on purchase intention and mediates the relationship between Live Shopping features and purchase intention. However, influencer credibility does not significantly influence trust, indicating that trust does not mediate the relationship between influencer credibility and purchase intention. These findings suggest that interactive shopping experiences provided through Live Shopping play a more substantial role in building consumer trust than influencer credibility. The study provides practical implications for digital businesses in optimizing social commerce strategies by enhancing Live Shopping quality and improving user experience.